2022
DOI: 10.1155/2022/4574218
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of Tribological Behaviour on DLC Coatings for AA5051 using DC Sputtering

Abstract: DLC coatings are deposited on aluminium substrates to improve the wear resistance property of the substrates using sputtering deposition in this study. DLC coatings are deposited using the graphite target onto the Al5051 substrates using DC sputtering. The deposited coatings are then analyzed for their adhesion strength, hardness, coefficient of friction, and chemical compositions. The pin-on-disk method is conducted in vacuumed conditions, dry air conditions (0% RH), and ambient air conditions (40% RH). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These coatings are used in parallel with molecular additives, which are proposed to adsorb on the DLC to reduce friction and help prevent wear. Previous studies on DLC have focused on tribological measurements. There is also some interest in biological systems such as protein and amino acid adsorption on fluorine-doped DLC. , There are a number of studies reported in the literature that have focused on the characterization of hydrogenated amorphous carbon; however, there have been considerably fewer studies on non-hydrogenated DLC.…”
Section: Introductionmentioning
confidence: 99%
“…These coatings are used in parallel with molecular additives, which are proposed to adsorb on the DLC to reduce friction and help prevent wear. Previous studies on DLC have focused on tribological measurements. There is also some interest in biological systems such as protein and amino acid adsorption on fluorine-doped DLC. , There are a number of studies reported in the literature that have focused on the characterization of hydrogenated amorphous carbon; however, there have been considerably fewer studies on non-hydrogenated DLC.…”
Section: Introductionmentioning
confidence: 99%
“…These films have earned their place as essential components in various industries. From enhancing the performance of cutting tools to ensuring the reliability of hard disk drives and even advancing the realm of biomedical devices, the impact of DLC-based films is undeniable [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%